2017
DOI: 10.1016/j.firesaf.2017.03.075
|View full text |Cite
|
Sign up to set email alerts
|

Thermal characteristics of externally venting flames and their effect on the exposed façade surface

Abstract: In a compartment fire, Externally Venting Flames (EVF) may significantly increase the risk of fire spreading to adjacent floors or buildings, especially when combustible insulation materials are installed on the building façade. An increasing number of recent reports suggest that existing fire engineering design methodologies cannot describe with sufficient accuracy the characteristics of EVF under realistic fire load conditions. In this context, a series of fire safety engineering design correlations used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Asimakopoulou et al. investigated externally venting flames (EVF) and their influences on fire spread on the exposed façade [ 15 ]. Using medium- and large-scale compartment-façade fire tests, they found that the proposed norm EN1991-1-2 underestimates the EVF centerline temperature.…”
Section: Phenomenon Of Firementioning
confidence: 99%
“…Asimakopoulou et al. investigated externally venting flames (EVF) and their influences on fire spread on the exposed façade [ 15 ]. Using medium- and large-scale compartment-façade fire tests, they found that the proposed norm EN1991-1-2 underestimates the EVF centerline temperature.…”
Section: Phenomenon Of Firementioning
confidence: 99%
“…16 Due to the increasing number of fire events in high-rise buildings 15,17 and the ever-stricter requirements for building thermal insulation, the fire safety characteristics of external façade systems has become an important issue. 18 Although several authors have highlighted the effect of the façade's geometric characteristics on the externally venting flame development and propagation, 17,19,20 literature reports on VF systems focus mainly on investigating their behaviour in terms of energy consumption reduction 2,3,6 ; only recently, there has been an effort to document the respective fire safety regulatory requirements and specification of use across Europe. 10 In this context, a façade fire performance assessment approach highlighted F I G U R E 1 General sketch of the PF (left) and the VF (right) system.…”
Section: Fire Risks Associated With Ventilated Façadesmentioning
confidence: 99%
“…Numerical investigations show that for a compartment fire, opening geometry [11] and prevailing ventilation conditions [12,13] severely impact the interior fire behaviour via oxygen availability and the development of externally venting flame. In the work of Asimakopoulou et al [14], an overall qualitative assessment of the correlations [15][16][17] is presented as compared to measurements obtained in large-scale façade fire tests. It is found that the correlations [15] originating from the experimental investigation of fire plumes significantly under-predict the external venting flame temperature and heat flux near the opening.…”
Section: Introductionmentioning
confidence: 99%
“…Limit work [1,2] has been conducted to describe the effects of the presence of sidewalls adjacent to an opening on the ventilation factor, and consequently, the propagation of ejected externally venting flame. A real ejected fire propagation [14] from the openings of the vertical U-shape building façade to the upper floors is shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%